If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(3 + k) = -5 + -5(8 + -6k) (3 * 3 + k * 3) = -5 + -5(8 + -6k) (9 + 3k) = -5 + -5(8 + -6k) 9 + 3k = -5 + (8 * -5 + -6k * -5) 9 + 3k = -5 + (-40 + 30k) Combine like terms: -5 + -40 = -45 9 + 3k = -45 + 30k Solving 9 + 3k = -45 + 30k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-30k' to each side of the equation. 9 + 3k + -30k = -45 + 30k + -30k Combine like terms: 3k + -30k = -27k 9 + -27k = -45 + 30k + -30k Combine like terms: 30k + -30k = 0 9 + -27k = -45 + 0 9 + -27k = -45 Add '-9' to each side of the equation. 9 + -9 + -27k = -45 + -9 Combine like terms: 9 + -9 = 0 0 + -27k = -45 + -9 -27k = -45 + -9 Combine like terms: -45 + -9 = -54 -27k = -54 Divide each side by '-27'. k = 2 Simplifying k = 2
| f=0.009(8) | | 7(m+3)=6(m+5)-8m | | 2x+5-x=45-7x | | 40a+20b=1250 | | y=15-(-4) | | x^2-3x-8=-4x+4 | | -6(n-2)-1=-(4+7n) | | -11n^2=9-2n | | 54m= | | 14g-5g-5g-3G=17 | | -3-3r=-6(5+5r) | | x^2-13x+39=3 | | x^2=3x-28 | | 3x-5=7x-45 | | -33-2b=-5+8(1-b) | | 2w-w+4w+w-5w=8 | | 5x+4=2y | | 6(4m-6)=30+2m | | sin(3x)-sin(7x)=0 | | -2x+17=-6(x+1)-5 | | 3m-2m-m+m=7 | | (1-3x)(9x-7)=0 | | -10x+8y=10 | | (x+1)2=144 | | 16+4r=7r+7 | | 15s-6s-6s=18 | | -8+5a=-93 | | 9x^2+4=-77 | | 5x+6y=226.19 | | 4x^2-25x+27=-4x+7 | | 27+x=68 | | 4s-3s=4 |